White Sapote Growing in the Home Landscape - Jonathan H. Crane; Carlos F. Balerdi (EDIS)
HS-1054, a 7-page fact sheet by Jonathan H. Crane and Carlos F. Balerdi, provides homeowners with a basic reference for growing white sapote in the home landscape. Tables include varieties in Florida, cultural practices by month, fertilizer recommendations and nutritional values. Published by the UF Department of Horticultural Sciences, November 2005.